Characterization of catalytic carboxylate triad in non-replicative DNA polymerase III (pol E) of Geobacillus kaustophilus HTA - Sandalli, C.; Singh, K.; Modak, M. J. (Cellular and Molecular Biology, 2012)
Three aspartic acid residues D378, D380 and D531 form the catalytic carboxylate triad in Geobacillus kaustophilus (Gka) DNA polymerase III α-subunit homolog, pol E. We cloned, expressed and purified wild type (WT), alanine (D → A) and glutamate (D → E) mutant enzymes of D378, D380 and D531. The WT and mutant enzymes were biochemically characterized for DNA binding, dNTP binding and catalytic activity in the presence of two metal ions (Mg2+ and Mn2+). The polymerase activity of all mutant enzymes was lost in the presence Mg2+, whereas D378E and D531E mutant enzymes showed about 35 and 60 percent activity, with Mn2+. D380E mutant enzyme did not show noticeable activity with either metal ions suggesting its absolute requirement in polymerase reaction. Kinetic characterization of individual mutant proteins showed that the template-primer binding affinity (KD.DNA) did not change due to both D → A or D → E mutation. The KM.dNTP for D378E and D531E increased by about 10- and 100-fold, compared to WT enzyme implicating the function of these residues in dNTP binding. Based on these results and the analysis of the available crystal structures of the homologous enzyme species in their apo and E.DNA.dNTP ternary complex forms, we conclude that D378 and D531 are mainly responsible for the binding of metal chelated substrate dNTP, while D380 is solely responsible for the chemical step of phosphodiester bond formation.